RETHINKING HOWARD M. FEDERSPIEL’S THESIS ON THE CONFLICT BETWEEN PERSATUAN ISLAM VS PERMOEFAKATAN ISLAM - Pepen Irpan Fauzan; Ahmad Khoirul Fata (Journal of Contemporary Islam and Muslim Societies, 2021)
Abstract: This article discusses the thesis written by Howard M. Federspiel on the conflict between Persatuan Islam (PERSIS) and Permoefakatan Islam. This present study employed the historical methods of heuristic, historical critic, interpretation, historiography to examine Federspiel’s thesis by pointing out the new facts related to the initial history of PERSIS and its relationship with Permoefakatan Islam. It reveals that Permoefakatan Islam was not part of PERSIS. It was an entirely separate organization established in 1924 to accommodate the aspirations of the old and young generations. It was not a reaction due to presence of A. Hassan in PERSIS. PERSIS’s reformist character had always been there since its establishment as an organization, and A. Hassan’s presence emphasized this character.Keywords: Federspiel, PERSIS, Permoefakatan Islam, A. Hassan